Does motivation mediate the relationship between competence perceptions and patient outcomes among individuals with chronic low back pain? A multiple mediation analysis. Issue 7 (27th March 2021) - Podlog, Leslie; Burns, Ryan; Dimmock, James A.; Jackson, Ben; Hall, Morgan S.; Fritz, Julie M.
Abstract: Purpose: The aim of this study was to examine: (1) motivations of patients with chronic low back pain to attend physical therapy; (2) relationships between competence perceptions, motivational regulations, and pain/disability; and (3) whether patient motivations to attend physical therapy mediate the relationship between competence perceptions and pain/disability. Methods: A sample of 64 participants completed baseline assessment (1-week prior to initiation of physical therapy) and 6-week follow-up assessment. Differences between motivation variables at baseline were examined using one-way within-person ANOVA. Relationships between competence perceptions, motivation subscales, and pain/disability were calculated using bivariate correlations and multiple mediation analyses. Results: Participants reported significantly higher levels of autonomous versus controlled motivation (mean difference = 3.5, p < 0.001, d = 2.3) and amotivation (mean difference = 3.6, p < 0.001, d = 2.4). Competence was positively associated with autonomous motivation ( r = 0.45, p ≤ 0.05) and negatively associated with controlled motivation ( r = −0.26, p ≤ 0.05), amotivation ( r = −0.57, p ≤ 0.05), pain ( r = −0.35, p ≤ 0.05), and disability ( r = −0.34, p ≤ 0.05). Amotivation significantly mediated the competence–pain relationship (Amotivation IE = −0.19, 95% CI (−0.44, −0.06), p < 0.05) and the competence–disability relationship (Amotivation IE = −0.07, 95% CI (−0.17, −0.01), p < 0.05). Conclusion: Findings highlight the role of competence perceptions in mitigating amotivation for physical therapy and the deleterious implications of amotivation for patient-centered outcomes. Implications for rehabilitation: While it is normal for patients to experience periods where they lack motivation for rehabilitation exercises, practitioners can encourage patients to assume responsibility for their recovery by informing them that amotivated states may increase the likelihood of increased pain perceptions and disability. Health-care practitioners should seek to foster competence perceptions in patients about to undergo physical therapy. Competence building strategies such as patient education, goal setting, and role modeling may be valuable in facilitating autonomous motivation and reducing amotivation for physical therapy.